DC And RF Characterization Of n-GaN Schottky Diode For Microwave Application - Munir, Tariq (2011)
Gallium nitride is a promising wide bandgap semiconductor material for high-power, high temperature and high frequency device applications. However, there are still a number of factors that are limiting the material to reach a satisfactory device performance. Among them the most important and critical factors are the reverse leakage current, series resistance, junction capacitance and thermal stability that limits Schottky diode performance on gallium nitride for Direct Current (DC) and Radio Frequency (RF) characteristics. To overcome these limitations we studied the influence of metal contact, contact area, thermal behavior and edge termination on DC and RF characteristics of n-GaN Schottky diode by simulation and fabrication approach.